2020
DOI: 10.7454/msk.v24i1.1164
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer vaccination awareness and acceptance among the females of Punjab, Pakistan

Abstract: Background: In developing countries like Pakistan, it is essential for health care professionals to have comprehensive knowledge regarding cervical cancer. Methods: A cross-sectional self-administered paper-based questionnaire was administered to patients from 2016 to 2018. This study included 200 females who attended the gynecological OPD of Lady Willingdon Hospital Lahore, Punjab. We evaluated cervical cancer knowledge, screening, prevention, and acceptance towards the vaccination. Data entry and analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…Hence; healthcare providers are abysmal healthcare promoter in our case it might be due to socio demographic covariates in rural and urban areas in this study. The knowledge was better than the study of Minhas et al 13 , this study revealed 3% knowledge about cervical cancer screening among females of Punjab, Pakistan. On the contrary Ozcan H et al; 23 revealed that 48.6% Turkstat had knowledge of screening of CA cervix and 16.2% received this knowledge from healthcare provider.…”
Section: A H E a D O F P R I N Tcontrasting
confidence: 76%
See 3 more Smart Citations
“…Hence; healthcare providers are abysmal healthcare promoter in our case it might be due to socio demographic covariates in rural and urban areas in this study. The knowledge was better than the study of Minhas et al 13 , this study revealed 3% knowledge about cervical cancer screening among females of Punjab, Pakistan. On the contrary Ozcan H et al; 23 revealed that 48.6% Turkstat had knowledge of screening of CA cervix and 16.2% received this knowledge from healthcare provider.…”
Section: A H E a D O F P R I N Tcontrasting
confidence: 76%
“…This study was approved by institutional ethical review board of BUMDC numbered 59/2021received on jan-2021. The sample size was calculated by the help of standard formula on the basis of 3% awareness of cervical cancer screening in Punjab Pakistan 13 as 45. Hence the intended sample size was 255 subjects as 105 cases and 150 controls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advancement in understanding cervical carcinoma has been effective in acknowledging its preventive nature (33). It is firmly known that effective screening and HPV vaccination, to a large extent, will significantly decrease the prevalence of the disease (33,34). For effective prophylaxis and screening, it is of paramount significance to understand the beliefs, perceptions, and knowledge of the general public.…”
Section: Discussionmentioning
confidence: 99%